2019
DOI: 10.1186/s41065-019-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptome analysis of H5N1 influenza virus-infected human cells

Abstract: BackgroundInfluenza A virus (IAV) belongs to the Orthomyxoviridae family. IAV causes a highly contagious respiratory disease in humans that exacts severe economic losses globally. The virus uses strategies developed to exploit and subvert cellular proteins and pathways to increase its own replication and to inhibit antiviral immune response.ResultsA/bar-headed goose/Qinghai/1/2005 (A/QH) was able to infect A549 and 293 T cells, with a high infection rate for A549 cells. To identify host cellular responses of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The cells were proliferated on glass coverslips, infected with B-SH (MOI = 0.1) until a monolayer of cells spread to > 80% of the bottom of the culture glass coverslips, incubated for 1 h, and then the inoculum was displaced with DMEM for continued incubation at 37˚C, 5% CO 2 . Cells were collected at 0, 4, 8, and 12 h, and the specific steps of immunofluorescence assay, as described by Jing et al [7] and Cao et al [15].…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
See 3 more Smart Citations
“…The cells were proliferated on glass coverslips, infected with B-SH (MOI = 0.1) until a monolayer of cells spread to > 80% of the bottom of the culture glass coverslips, incubated for 1 h, and then the inoculum was displaced with DMEM for continued incubation at 37˚C, 5% CO 2 . Cells were collected at 0, 4, 8, and 12 h, and the specific steps of immunofluorescence assay, as described by Jing et al [7] and Cao et al [15].…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
“…In our previous reports, migratory birds could also carry and spread H5N1 A/QH virus, which is likely the reasons for human infections throughout China and Europe over the past several years. We tried to analyze and compare the common genes regulated by IAV and IBV infection in A549 cells, and we found that there were very few common genes, so the infection processes of these two viruses differ [15,[49][50][51]. Compared to B/Victoria, there were differences between the two strains, and individual specific strains can reflect idiosyncratic specific effects.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Previously, transcriptome analyses of host-pathogen interactions were conducted on the viral infections including herpesvirus [ 11 ], cytomegalovirus [ 12 , 13 ], influenza virus [ 14 ], human respiratory syncytial virus [ 15 ], measles virus [ 16 ], rubella virus [ 17 ], dengue virus [ 18 ], rabies virus [ 17 ], ebolavirus [ 19 , 20 ], and human immunodeficiency virus (HIV) [ 21 ]. Moreover, studding the transcriptome of Calu-3 cell line (human lung cancer cell line) after infection with severe acute respiratory syndrome coronavirus (SARS-CoV) revealed that recognition receptors and the interleukin 17 (IL-17) pathway were activated [ 22 ].…”
Section: Introductionmentioning
confidence: 99%